In vitro and in vivo Pharmacological Studies of Leaves of Staurogyne argentea Wall. - Chowdhury, Suhana Manzur; Sultana, Irin; Kuddus, Md Ruhul; Ibrahim, Mohammed (Bangladesh Pharmaceutical Journal, 2023)
Staurogyne argentea Wall. (Family: Acanthaceae) is an important medicinal plant that has many traditional uses in tribal areas of Bangladesh. The current study emphasizes the pharmacological investigations of n-hexane, chloroform and aqueous soluble fractions of ethanol extract of leaves of S. argentea to justify the traditional uses of this plant species in Bangladesh. In vitro anti-inflammatory activity of S. argentea was confirmed by inhibition of egg albumin denaturation and erythrocyte membrane stabilizing methods. In both experiments, the aqueous fraction at concentration of 160 μg/ml exhibited significant inhibition of egg albumin denaturation by 76.91% with IC50 value of 24.22 μg/ml compared to standard Diclofenac-Na. In membrane stabilization assay, the aqueous fraction showed prominent anti-inflammatory activity by protecting the human erythrocyte membrane against hypotonic solution induced lysis. In addition, among all the aqueous fraction at 100 μg/ml also showed maximum antioxidant potential via the inhibition of DPPH scavenging by 75.05% (IC50= 42.92 μg/ml). The test materials were subjected to evaluate for the anti-diabetic activity by both in vitro starch iodine method as well as by oral glucose tolerance test in Swiss albino mice. In both experiments, the aqueous fraction showed maximum blood glucose lowering activity which is comparable to standard glibenclamide. The chloroform fraction (Conc. 500 mg/kg bw) exhibited moderate inhibition of both acetic acid-induced writhing reflex and yeast-induced pyrexia in mice. During sedative activity screening, different solvent fractions produced mild to moderate activity in comparison with standard diazepam. These findings revealed that S. argentea is a valuable source of bioactive compounds with diverge pharmacological actions, which validates its use in Bangladesh folk medicinal practices. Bangladesh Pharmaceutical Journal 26(1): 89-98, 2023 (January)